Functionalized Graphene Oxide Shields Tooth Dentin from Decalcification. (February 2020) - Nizami, M.Z.I.; Nishina, Y.; Yamamoto, T.; Shinoda-Ito, Y.; Takashiba, S.
This in vitro study assessed the efficacy of functionalized graphene oxide (f-GO) nanocomposites on the decalcification of dentin, because dental caries of the root surface is becoming one of the new problems in aged society. Hydroxyapatite plates (HAP) and dentin slices were coated with f-GO nanocomposites by comparing them to silver diamine fluoride as a positive control, then treated with decalcification solutions such as ethylenediaminetetraacetic acid and citrate at 37°C for 24 h. Scanning electron microscopy (SEM) revealed significant protection of the surface morphology of HAP and dentin. On the other hand, a cariogenic Streptococcus mutans growth was inhibited by f-GO nanocomposites. In addition, cytotoxicity of them to epithelial cells was much less than that of povidone-iodine, which is commonly used for oral disinfectant. We synthesized 5 different f-GO nanocomposites such as GO–silver (Ag), GO-Ag–calcium fluoride (CaF2 ), GO-CaF2, GO-zinc, and GO–tricalcium phosphate (Ca3 (PO4 )2 ). They were standardized by evaluating under SEM, transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), thermogravimetry analysis (TGA), and Raman spectra after being synthesized in an aseptic technique. The abilities of GO-Ag, GO-Ag-CaF2, and GO-CaF2 nanocomposites were most preventive for decalcification. In addition, GO-Ag and GO-Ag-CaF2 almost completely inhibited S. mutans growth. However, they did not exhibit cytotoxicity to epithelial cells except at the highest concentration (0.1 w/v%) of GO-Ag and GO-Ag-CaF2 . Furthermore, these f-GO nanocomposites exhibited less or no discoloration of dentin, although commonly used silver diamine fluoride causes discoloration of dentin to black. Thus, these f-GO nanocomposites are useful to protect dental caries on the tooth root that becomes a social problem in aged society.